Approaches to implementing and financing primary health care in Kenya: a case of seven counties - Janette Karimi; Salim Hussien; Elizabeth Wangia; Mercy-Irene Kimani; Mohamud Mohamed; Melissa Wanda; Rosemarie Muganda; Rachel Ndirangu; Daniel Mwai; Mercy Wanjala; Fadhila Richter (Frontiers in Health Services)
BackgroundKenya has prioritized Primary Health Care as an indispensable foundation to realize UHC by 2022. Integral to this approach’s operationalization is the adoption of the primary health care networks (PCNs) model to strengthen service delivery efficiency and coordination. The PCNs are coordinated by a Multidisciplinary Team (MDT). The MDT is dynamic and should comprise a care and support team that matches patient health needs and the catchment population. This scholarly article delineates the outcomes of an investigative assessment reviewing the current state and trajectory of PHC implementation, focusing on the PCN implementation, and analyzing PHC financing modalities in 7 counties in Kenya.MethodsThis study employed a mixed-methodological approach to gather data from seven counties; Garissa, Nyeri, Makueni, Vihiga, Kisumu, Nakuru, and Mombasa. Key informant interviews were conducted with county health officials and partners. Additionally, counties were supplied with templates for qualitative data. Data was subsequently analyzed using thematic analysis and descriptive statistics.ResultsSuccessful implementation of PCNs was positively correlated with robust county-level leadership, prioritization of PHC funding, intersectoral collaboration, and joint planning initiatives. Counties which had achieved high levels of community health unit (CHU) establishment and functionality were more adept at successfully mapping and operationalizing PCNs. All participating counties adopted Sub-County Health Management Teams (SCHMTs) as the MDTs due to staffing limitations at primary care facilities consequently inhibiting the capacity for effective MDT engagement. Fiscal commitments at the county level were imperative for facilitating the mobility of MDTs and orchestrating community outreach initiatives. Reimbursements from the National Hospital Insurance Fund (NHIF) served as a pivotal financial conduit for the sustenance of primary care facilities.ConclusionThe study finds that robust leadership, funding, collaboration, and planning were crucial for the effective operationalization and financial structuring of PCNs. The study recommends that the county governments should invest more in PHC infrastructure, equipment, and supplies, as well as in strengthening the capacity and mobility of MDTs. The study also suggests that uptake of NHIF will enhance the sustainability of PCNs.